In memoriam Professor Dr. Rusli Ismail / Associate Prof. Dr. Mahmathi Karuppannan - Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
It is with heavy hearts that we share the news of the passing of Professor Dr. Rusli Ismail. In the world of pharmacy and healthcare education, certain individuals shine as beacons of inspiration. Professor Dr. Rusli Ismail, whose journey was as distinguished as it was impactful, is undoubtedly one of them. Professor Rusli was a visionary, whose contributions have reshaped the landscape of pharmacy practice and education in Malaysia and beyond. Professor Rusli began his career at Universiti Sains Malaysia (USM), where he blazed trails by establishing the country's first clinical pharmacokinetics and therapeutic drug monitoring (TDM) service. This pioneering effort has left an enduring mark, as nearly all major hospitals in our country now boast of such critical services. His dedication to advancing the field of pharmacy led him to play a pivotal role in the development of clinical pharmacy and the Master in Pharmacy (MPharm) program in clinical pharmacy. He made significant contributions during his tenure at USM (School of Medical Sciences, School of Pharmaceutical Sciences, and Institute for Research in Molecular Medicine, InForMM), Universiti Malaya, Universiti Sultan Zainal Abidin, and several other esteemed institutions. We also remember Professor Rusli's invaluable role as an academic advisor for the Faculty of Pharmacy at UiTM.